Research Progress and Prospects on Risk Assessment and Early Warning for Embankment Safety in Estuarine and Coastal Areas - ZHU Yong-hui, LI Meng-yu, LUAN Hua-long, QU Geng, YUAN Yuan, WU Wei-wei, GE Jian-zhong, GUO Jun (长江科学院院报)
In recent years, under the combined effects of intensified human activities, climate change, and sea level rise, estuarine and coastal areas have faced increasing risks of extreme flood-tide damage, posing a serious threat to the safety of estuarine and coastal embankments. Due to the complex and rapidly changing dynamic conditions, multiple disaster-causing factors, and the abrupt and strongly destructive nature of related processes, research on embankment safety risk assessment and disaster early warning has become increasingly challenging. This represents an interdisciplinary research frontier and hotspot in the field of disaster prevention and mitigation that has attracted global attention. Focusing on international research hotspots in embankment safety risk assessment and early warning and strategic needs for disaster prevention and mitigation at the national level, this study systematically reviews the current status and trends of embankment safety risk assessment and early warning technologies both domestically and internationally. Additionally, it identifies the key scientific and technical challenges that require urgent solutions. Based on the limitations of existing research, this study proposes suggestions and future research directions. The study integrates approaches from multiple disciplines, including estuarine and coastal science, coastal dynamics, river dynamics, hydrology, meteorology, engineering geology, geophysics, information engineering, and computer engineering. By employing field surveys, dynamic monitoring, flume experiments, numerical simulation, machine learning, and theoretical analysis, it clarifies three key relationships driven by the evolution mechanism of the flood-tide disaster chains: the “fluid-structure interaction”, “causal relationship between disaster-causing factors and risk assessment”, and “coordination between habitat safety and dynamic early warning”. From the perspective of hydrometeorological conditions, disaster chain evolution, and fluid-structure interaction, this study reveals the evolution mechanism of flood-tide disaster chains under changing conditions and the response mechanism for embankment disasters. Furthermore, from the perspective of multi-element monitoring and multi-indicator dynamic early warning, the study establishes a comprehensive embankment safety risk assessment system and early warning model for estuarine and coastal areas, with technical applications to enhance the accuracy of disaster forecasting and the resilience of embankment protection. The research findings are expected to improve the safety assurance capabilities in estuarine and coastal areas, significantly enhance early warning of embankment disaster risks, and provide critical scientific and technological support for evidence-based decision-making in disaster prevention and mitigation.